The relationship between personality traits and innovative work behavior at Arl Bowl Sdn Bhd in Putrajaya, Malaysia / Nurul Husna Kamrud Din - Kamrud Din, Nurul Husna (Faculty of Business and Management, 2018)
The main objective of this research paper was to investigate the relationship between personality traits and innovative work behavior among employees in ARL Bowl Sdn Bhd. This research paper also aim to determine of influence of personality traits and innovative work behavior employees. Questionnaire was being used as the instrument to collect data needed in order to complete this research paper. In this research paper, no pilot test is required at this level of study. SPSS V-23 was used to analyze the questionnaire in order to determine the findings of the research. Then, the total of population number of employees approximately about 50 people but only 44 employees were chosen as the respondents in the research conducted. The research was using table from Krejcie and Morgan (1970) in order to determine the sample size. This research paper used simple random sampling as the sampling technique. In this research paper, there have three of research objective, eight research question and six hypothesis. Based on the finding, there have no relationship between personality and innovative work behavior in ARL Bowl Sdn Bhd, Putrajaya. There are some recommendation that can be implementing by ARL Bowl Sdn Bhd to achieve strong relationship between personality traits and innovative work behavior in the organization. Lastly, for future researcher they should study at different sector and make sure choose the company that already long in industry to find the variety of the finding in their work.